2013
DOI: 10.1111/ijs.12169
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Direct Current Stimulation (tDCS): Does it Have Merit in Stroke Rehabilitation? A Systematic Review

Abstract: Transcranial direct current stimulation has been gaining increasing interest as a potential therapeutic treatment in stroke recovery. We performed a systematic review with meta-analysis of randomized controlled trials to collate the available evidence in adults with residual motor impairments as a result of stroke. The primary outcome was change in motor function or impairment as a result of transcranial direct current stimulation, using any reported electrode montage, with or without adjunct physical therapy.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
110
2
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(122 citation statements)
references
References 27 publications
7
110
2
3
Order By: Relevance
“…Previous meta-analysis studies reported that balanced cortical activity between M1 of the hemispheres following tDCS or rTMS protocols may contribute to motor improvements in paretic limbs (e.g., various clinical assessments or activities of daily living) [25][26][27][28]. However, Chhatbar and Feng pointed out that these meta-analytic findings are still susceptible to inconsistency in outcome measures as well as selection criteria [29].…”
Section: Introductionmentioning
confidence: 99%
“…Previous meta-analysis studies reported that balanced cortical activity between M1 of the hemispheres following tDCS or rTMS protocols may contribute to motor improvements in paretic limbs (e.g., various clinical assessments or activities of daily living) [25][26][27][28]. However, Chhatbar and Feng pointed out that these meta-analytic findings are still susceptible to inconsistency in outcome measures as well as selection criteria [29].…”
Section: Introductionmentioning
confidence: 99%
“…У больных с достаточным уровнем сотрудничества возможно проведение функцио-нальной нейровизуализации с последующей ТМС выявленных зон активации. Несмотря на отдельные позитивные данные исследований, эффективность ТЭС в реабилитации больных, перенесших инсульт, остается недоказанной (2b) [17].…”
Section: аппаратная вертикализацияunclassified
“…Несмотря на отдельные позитивные данные исследований, эф-фективность этого метода в реабилитации больных, перенесших инсульт, остается не доказанной [18].…”
Section: немедикаментозные методы восстановления после инсультаunclassified